IMPLEMENTASI KEBIJAKAN PEMERINTAH TENTANG MONEY LAUNDRY - Junaidi, Junaidi (Aspirasi: Jurnal Ilmiah Administrasi Negara, 2018)
The crime of money laundering has become one of the crimes that get serious attention from the international community. This crime always accompanies an organized crime that can cross national borders such as narcotics crime, terrorism, and corruption. Although the state has issued new regulations to prevent the occurrence of money laundering crimes, but it turns out more money laundering practices with an increasingly varied mode. The crime of money laundering began to emerge and legally regulated in Indonesia since 17 April 2002 through the enactment of Law no. 15 Year 2002 on the Crime of Money Laundering. The law is the first legal rule governing money laundering offenses. In Indonesia, the regulation on money laundering has undergone several changes. A year after the birth of Law no. 15 of 2002 on Money Laundering, the Act was amended through Law no. 25 of 2003. It still needs to be optimized, in 2010, came another law, the Law no. 8 of 2010 on Prevention and Eradication of Money Laundering Criminal Act (UU TPPU) which contains some improvements from the previous Law. Based on the PPATK 2013 Annual Report, 12 decisions related to money laundering cases and if accumulated from 2005 to 2013, there are 105 cases that have been terminated. A similar report came from the Supreme Court. According to the highest court institution in 2010, as many as 11 cases that entered the Supreme Court stage, in 2011 there were 19 cases and in 2013 there were only nine cases. The whole is a case accepted by the Supreme Court at the Cassation level.